METODE PEMBELAJARAN AKHLAK MENURUT K. H. AHMAD DAHLAN DAN RELEVANSINYA DENGAN PEMBELAJARAN AKHLAK DALAM ISLAM (TINJAUAN WACANA BAHASA INDONESIA) - Agus Hi Jamal; Mulkhan, Abdul Munir; Zamah Sari (Literasi: Jurnal Ilmiah Pendidikan Bahasa, Sastra Indonesia dan Daerah, 2025)
ABSTRACT This study is entitled "The Method of Learning Morals According to K.H. Ahmad Dahlan and Its Relevance to Moral Learning in Islam Review of Indonesian Language Discourse". The purpose of this study is to find out and understand the concept of morals and the method of learning morals taught by K.H. Ahmad Dahlan, and to explain the relevance between the concept and method to moral learning in Islam. The method used in this study is library research, by collecting data from primary and secondary sources, including books and articles about K.H. Ahmad Dahlan. The results of the study show that K.H. Ahmad Dahlan emphasized the importance of adhering to the Qur'an and Sunnah in everyday life, and used the habituation method in teaching morals to his students. The concept of morals and the method of learning morals according to K.H. Ahmad Dahlan are relevant to the principles of morals in Islam, which shows the harmony between his teachings and broader Islamic values. This research is expected to contribute to the understanding of morals and moral learning methods in the context of Islamic education, as well as adding to the intellectual treasury of K.H. Ahmad Dahlan's thoughts. Keywords: Learning, Morals, its relevance to Indonesian Language discourse